Effects of Financial Inclusion on Startup Establishment in OECD Countries - Van, Dinh Thi Thanh; Trang, Nguyen Thuc (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 34 No 1, 2018)
Financial inclusion and startup are two topics, which recently get attention of academic researchers and policy makers in Vietnam. One of the important factors for setting up a successful startup is the financial capability of the owners. Therefore, financial inclusion has a strong correlation with startup establishment. This article tested the effects of several factors in financial index (findex) developed by World Bank on startup establishment in some OECD countries. The result showed that borrowing from friends and relatives along with from credit institutions and opening a debit account at banks have  significant impacts on startup establishment in these countries. Finally, the article presented several recommendations for policy makers to stimulate the startup growth in Vietnam in the next time.